Potential Energy of Pretext: Structural and Compositional Features of “Isaac and Abraham” by Joseph Brodsky - O. V. Bogdanova; T. N. Baranova (Научный диалог)
An interpretation of the well-known, but rarely used for a holistic analysis of the work of I. Brodsky “Isaac and Abraham” is proposed in the article. If Brodsky’s text is traditionally viewed as a poetic retelling of the Old Testament history in a modern way, then the authors propose a different perspective of textual perception - free reflections of a lyrical subject, a modern hero, over an ancient sacred text. As a result, the claims of critics regarding the “chaotic” and “congested” Brodsky’s text are removed, in contrast, the harmony and depth of reflection of the lyrical subject, the modern heropoet, are demonstrated. In the course of the analysis, the genre qualification of “Isaac and Abraham” was clarified - not as a poem (the traditional point of view), but as a “great poem” (I. Brodsky’s autopresentation). Deciphering of the “difficult” places of the poem - images of a bush, a board, a train, etc., as it seemed to critics, was artificially introduced by Brodsky into the text and violated the integrity of the work. It is argued that the poem “Isaac and Abraham” was not a transcription of the Bible, but an attempt by the maturing Brodsky from today to comprehend the sacred text and on its basis comprehend himself, penetrate into the dark past in order to see the present more clearly.